Involvement of Salicylic Acid in the Establishment of the Rhizobium meliloti-Alfalfa Symbiosis - F. Martínez-Abarca; J. A. Herrera-Cervera; P. Bueno; J. Sanjuan; T. Bisseling; J. Olivares (Molecular Plant-Microbe Interactions, 1998)
Inoculation of alfalfa plants with either incompatible Rhizobium or a Rhizobium mutant blocked in Nod factor synthesis led to an accumulation of salicylic acid in roots, in contrast to plants inoculated with a wild-type (compatible) R. meliloti strain. When salicylic acid was exogenously applied prior to inoculation of alfalfa plants with either purified Nod factor or compatible Rhizobium strains, a significant inhibition of nodule primordia formation and a reduction of the number of emerging nodules, respectively, as well as a delay in nodule visualization, were observed. These results suggest an involvement of Rhizobium-synthesized Nod factors in the inhibition of salicylic acid-mediated defense in legumes.